AB0717 The Comparison of Retinal Vascular Changes and Nailfold Capillaroscopic Findings in Patients with Scleroderma. (9th June 2015) - Ozmen, M.; Akin Sari, S.; Koc, F.; Can, G.; Sahin Atik, S.; Tomas, N.; Yurdakul, N.; Akar, S.
Abstract : Background: Scleroderma is a multisystem connective tissue disease characterized by cutaneous and visceral fibrosis and obliterative vasculopathy of small arteries (1). Microvascular changes can be detected by nailfold capillaroscopy in patients with scleroderma (2). Retina is a window to analyse microvascular changes in some diseases, like diabetic retinopathy (DRP) (3). Objectives: It was aimed to assess retinal microvascular changes and to analyse association between these changes and nailfold capillaroscopic findings in patients with scleroderma. Methods: Thirty-five patients with scleroderma, who met 1980 ACR classification criteria, were studied. Twenty-six patients with DRP and 32 healthy individuals were studied as disease and healthy control group, respectively. Nailfold capillaries of all participants were assessed by videocapillaroscopy. 90D lens and Goldmann three-mirror goniolens were used for retinal examination. Results: Median age was 48 (24-69) years, 56 (28-68) years and 47 (25-64) years in patients with scleroderma, patients with DRP and healthy control group, respectively (p=0.02: due to DRP group). Female:male ratio was 32:3 (91%:9%), 22:4 (85%:15%) and 28:4 (88%:12%) in patients with scleroderma, patients with DRP and healthy group, respectively (p=0.86). Median disease duration was 3 (0-11) years and 2 (0-13) years in patients with scleroderma and patients with DRP, respectively. Twenty-four (68%) patients with scleroderma had limited, 11 (32%) patients had diffuse disease. Thirteen (37%), 10 (29%) and 12 (34%) patients with scleroderma had early, active and late capillaroscopic scleroderma pattern, respectively. While 21 (81%) patients with DRP had non-proliferative, 5 (19%) patients with DRP had proliferative disease. The capillaroscopic findings were not statistically different between patients with proliferative and non-proliferative DRP (p>0.05). While there was no pathological retinal finding in healthy individuals, 4 (11%) patients with scleroderma had pathological findings: two patients with microaneurysm, one patient with retinal thinning and one patient with slight narrowing of the arteries. When patients with and without pathological retinal findings were compared, there was no statistically difference in terms of capillaroscopic findings (giant capillary, microbleeding, capillary lost, microarchitecture irregularity. avascular area, capillary tortuosity, apical and capillary diameter). Conclusions: This study revealed retinal vascular changes in patients with scleroderma. But there was no association between these changes and nailfold capillaroscopic findings. Retinal examination is easy to perform and it may give some useful informations about vascular involvement in patients with scleroderma. Further studies are needed to evaluate clinical and prognostic value of retinal findings. References: Medsger TA Jr. Systemic sclerosis (scleroderma): clinical aspects. In: Koopman WJ, ed. Arthritis and allied conditions: textbook of rheumatology. Baltimore: Williams and Wilkins 1997:1433–64. Cutolo M. Assessing microvascular changes in systemic sclerosis diagnosis and management. Nat Rev Rheumatol 2010;6:578-87. Moss SE. Comparison between ophthalmoscopy and fundus photography in determining severity of diabetic retinopathy. Ophthalmology 1985; 92(1):62. Disclosure of Interest: None declared